Study of the Influence of Uniaxial Strain and Electron Irradiation on the Deformation of Polytetrafluoroethylene Film; Key Engineering Materials; Vol. 781 : Radiation-Thermal Effects and Processes in Inorganic Materials - Kupchishin A. I. Anatoliy Ivanovich; Niyazov M. N. Marat; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Voronova N. A. Nataliya; Kupchishin A. A. Alexander (2018, 2018)
Title screen